Uji Aktivitas Antioksidan Kombucha Daun Kelakai (Stenochlaena palustris (Burm.F) Bedd) Dengan Metode DPPH - Hidayatullah, Muhammad; Abdurrahman, Abdurrahman; Andina , Lisa; Astiati , Rini; Rina, Rina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Degenerative diseases are often caused by exposure to free radicals, and antioxidants play an important role in maintaining body stability by counteracting them. Kelakai (Stenochlaena palustris), a typical plant of Kalimantan, contains bioactive compounds such as phenolics and flavonoids, making it a potential source of natural antioxidants. This study aims to determine the results of antioxidant activity tests on kelakai leaf kombucha. Kombucha was chosen because its antioxidant activity is influenced by the phenolic content formed during fermentation, potentially becoming an antioxidant-rich probiotic drink. The antioxidant activity test of kelakai leaf kombucha used the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results of determining the maximum absorption wavelength of 0.1 mM DPPH were at 515 nm with the highest absorption of 0.602. The antioxidant activity test using quercetin as a comparison resulted in an IC₅₀ value of 3.0892 ppm. This quercetin IC₅₀ value is included in the very strong category (<50 ppm). Meanwhile, the antioxidant activity test on kelakai leaf kombucha yielded an IC₅₀ value of 0.5845 ppm. This value also indicates that kelakai leaf kombucha has very strong antioxidant activity. Increasing sample concentration is directly proportional to the increase in antioxidant activity, as indicated by a decrease in the absorption value. Therefore, the development of kelakai leaf kombucha and testing its antioxidant activity are expected to produce innovative functional food products.